Essentials in stable angina pectoris - Kaski, Juan Carlos (Springer, 2016)
This book discusses the management of stable angina pectoris, with a focus on pharmacotherapy. Traditional angina triggered by obstructive coronary artery disease is tackled in the book, along with specific discussions of non-atherosclerotic forms of angina pectoris, such as microvascular angina. Several aspects of microvascular angina are presented in this work, including its clinical presentation and prognosis, and the diagnostic tests used in clinical practice and management. Presented within this monographic work are current treatments as recommended by international guidelines, but also introduced are new concepts regarding unmet needs in the management of patients with chronic stable angina whether triggered by coronary artery disease or by coronary microvascular dysfunction. The ultimate aim of Essentials in Stable Angina Pectoris is to assist the managing physician to identify the different forms of angina pectoris that may come to their attention, all of which pose important diagnostic and therapeutic challenges. This work also includes clinical diagnostic and therapeutic algorithms, thus bringing this topic closer to the practicing cardiologist.